Growing Brands Through Sponsorship: An Empirical Investigation of Brand Image Transfer in a Sponsorship Alliance - Gross, Philip (Springer, 2015)
​Philip Gross addresses a new opportunity for growing brands that may reside within a sponsorship alliance. Typically, brands vie for image transfer from an event or other property when entering a sponsorship engagement. Yet this practice leaves a valuable part of a sponsorship alliance unexploited. Specifically, the author infers from theories of social and cognitive psychology to propose and test a research model that accounts for a sponsor to also gain from brand attitude and personality traits innately tied to a co‑sponsor of the same event. The results provide evidence for direct image transfer between two sponsor brands. Hence, pairing with a co‑sponsor might fortify or dilute a sponsor brand's image depending on the expediency of the image conveyed by that ally.